Failure Assessment Diagram (FAD) analysis of fatigue test results for X65 welded joints - Hoh, Hsin Jen (2018)
Offshore pipelines transfer oil and gas from seabed to production facility on the surface. The long pipelines are formed by welding of pipe segments, where these welded joints are a source of stress concentration and defects from which fatigue cracks can grow. This work aims to study the behaviour of deep fatigue cracks. In this current work, finite-element based on a parametric study of four-point bending is used to assess the stress intensity factors (SIFs) of deep surface cracks in X65 specimens, while considering local limit load the remaining load bearing ligament. These deep cracks take on a non-regular shape and have widths that exceed that of the specimen. They will be compared to empirical expressions from derived standards such as British Standards BS7910, which may be more conservative. The existing large flaw is also assessed via the failure assessment diagram (FAD). The effects of limit load solutions and reference stresses used to determine the FAD diagram will be discussed.